A Bioinspired Stretchable Sensory‐Neuromorphic System. Issue 44 (12th September 2021) - Kim, Sun Hong; Baek, Geun Woo; Yoon, Jiyong; Seo, Seunghwan; Park, Jinhong; Hahm, Donghyo; Chang, Jun Hyuk; Seong, Duhwan; Seo, Hyunseon; Oh, Seyong; Kim, Kyunghwan; Jung, Heeyoung; et al.
Abstract: Conventional stretchable electronics that adopt a wavy design, a neutral mechanical plane, and conformal contact between abiotic and biotic interfaces have exhibited diverse skin‐interfaced applications. Despite such remarkable progress, the evolution of intelligent skin prosthetics is challenged by the absence of the monolithic integration of neuromorphic constituents into individual sensing and actuating components. Herein, a bioinspired stretchable sensory‐neuromorphic system, comprising an artificial mechanoreceptor, artificial synapse, and epidermal photonic actuator is demonstrated; these three biomimetic functionalities correspond to a stretchable capacitive pressure sensor, a resistive random‐access memory, and a quantum dot light‐emitting diode, respectively. This system features a rigid‐island structure interconnected with a sinter‐free printable conductor, which is optimized by controlling the evaporation rate of solvent (≈160% stretchability and ≈18 550 S cm −1 conductivity). Devised design improves both areal density and structural reliability while avoiding the thermal degradation of heat‐sensitive stretchable electronic components. Moreover, even in the skin deformation range, the system accurately recognizes various patterned stimuli via an artificial neural network with training/inferencing functions. Therefore, the new bioinspired system is expected to be an important step toward implementing intelligent wearable electronics. Abstract : A novel form of stretchable integrated system, namely a bioinspired stretchable sensory‐neuromorphic system, is presented, which comprises an artificial mechanoreceptor, an artificial synapse, and an epidermal photonic actuator as three devices. This system features a bioinspired sensory‐neuromorphic system entailing tactile sensing, pattern learning/inferencing, and visualizing feedback information.